Key considerations in setting up a therapeutic plasma exchange service for neurology patients - Nicole Japzon; Aneliya Takova; Viva Levee; Ruth Han; Jenny McDonald; Benjamin Sacks; Sinead Rosser; Katharine Hunt; Laura Zambreanu; Michael Lunn; Jennifer Spillane (Advances in Clinical Neuroscience & Rehabilitation)
Therapeutic plasma exchange (TPE) is effective in the treatment of both neurological and non-neurological diseases. It is highly efficacious when used appropriately but has significant associated risks. We outline the key components for consideration when setting up and maintaining a TPE service based on our experience at the National Hospital for Neurology and Neurosurgery (NHNN), a tertiary centre dedicated to the diagnosis and management of neurological diseases. This includes the assessment of vascular access choice, anticoagulation, replacement fluid and review of patient selection and pathways. We also consider the creation of hospital guidelines and the provision of patient and staff education for developing the service. We aim to outline a service model for other centres to provide a safe and effective TPE pathway.